Contending with destiny : the Caribbean in the 21st century - Hall, Kenneth (Ian Randle Pub. KingstonJM, 2000)
Focuses on the challenges facing the region and identifies strategic responses which could inform policy. Covers a wide spectrum of issues ranging from broad philosophical concerns relating to the conception and definition of the Caribbean, the validity of conventional assumptions and categories of analysis to more specific questions such as: economic policy options; governance structures; science and technoology, including information technology; education; social integration; political theory; international relations; gender; art; literature and the creative imagination.